Peningkatan Keterampilan Pengasuhan pada Orang Tua untuk Mengoptimalisasi Tumbuh Kembang Anak - Taib, Bahran; Banafif, Ahmad Syakur; Lasepta, Esterina; Hartini, Hartini; Purwadi, Purwadi (EDUKASI, 2023)
The majority of the Shaman community is still unfamiliar with appropriate parenting patterns to optimize the development and growth of early childhood. So it is necessary to carry out socialization activities regarding parenting skills. The aim of this activity is so that parents in Dukun District, Magelang Regency, Central Java can understand and apply appropriate parenting patterns in order to optimize children's growth and development through stimulation and nutritious food. The target of the activities are PAUD teachers and parents of PAUD students in Aisyiyah District, Dukun District. Magelang-Central Java. The activity implementation procedure starts from activity planning, observation and preparation of the tools and materials needed, presentation of material by resource persons to participants, discussion between presenters and participants and then ends with activity evaluation. The number of participants who attended was 130 people. As a result of this outreach activity, participants were very enthusiastic about listening so that the level of public awareness and understanding increased about the importance of parenting skills in optimizing children's growth and development. Apart from that, the community is also aware that parenting skills for children is a problem that should receive attention from various parties because inappropriate parenting patterns can hinder children's optimal growth and development and of course can have long-term effects on the child's personality